1994
DOI: 10.1111/j.1476-5381.1994.tb13180.x
|View full text |Cite
|
Sign up to set email alerts
|

Loss of preconditioning in rabbits with vascular tolerance to nitroglycerin

Abstract: A preceding right ventricular overdrive pacing (VOP) of 500 b.p.m. for 5 min, markedly reduced the severity of global myocardial ischaemia produced by a subsequent 5-min VOP in conscious rabbits. This VOP-induced preconditioning developed in parallel with an increase in cardiac cyclic guanosine 3':5'-monophosphate (cyclic GMP) content. VOP-induced preconditioning was abolished when the animals had been made tolerant to the vasodilator effect of nitroglycerin (NG). In the heart of the NG-tolerant rabbits, neith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 7 publications
2
20
0
Order By: Relevance
“…Fakete et al [27] also reported the loss of protection by IPostC in isolated rat hearts in which nitrate tolerance was induced by the administration of nitroglycerin 3 days before the ischemic insult. Similar findings were obtained in a rabbit model; in that study, nitrate tolerance abolished the protection afforded by IPreC [28,29]. Together, these results highlight the important role of NO in the intracellular signal transduction mechanism of IPreC and IPostC [30,31].…”
Section: Discussionsupporting
confidence: 86%
“…Fakete et al [27] also reported the loss of protection by IPostC in isolated rat hearts in which nitrate tolerance was induced by the administration of nitroglycerin 3 days before the ischemic insult. Similar findings were obtained in a rabbit model; in that study, nitrate tolerance abolished the protection afforded by IPreC [28,29]. Together, these results highlight the important role of NO in the intracellular signal transduction mechanism of IPreC and IPostC [30,31].…”
Section: Discussionsupporting
confidence: 86%
“…We have recently reported that a significant decrease in cardiac NO content assessed by electron spin resonance (ESR) abolished pacing-induced preconditioning in rat heart (Ferdinandy et al 1996). We have also shown that the cardioprotective effect of pacing-induced preconditioning was proportional to the elevation of myocardial cGMP content (Szilvassy et al 1994a), and that the reduced cardiac cGMP content due to experimental nitroglycerin tolerance led to the loss of preconditioning in rabbits (Szilvassy et al 1994b). These data suggest that the NO-cGMP pathway may be involved in the mechanism of pacing-induced preconditioning in rabbits and rats, however, the major source of NO in the heart has not been identified.…”
Section: Introductionmentioning
confidence: 96%
“…In this series of studies, changes in whole body insulin sensitivity were assessed by the RIST method in conscious animals, an approach specifically proposed to investigate the effect of food on insulin sensitivity 14 . Development of vascular tolerance to GTN was confirmed on the 7 th day by testing endothelium free carotid artery rings for isometric tension as described previously 5,6 . Rings of 5 mm in length were precontracted with an EC 50 concentration of norepinephrine in addition to a resting tension of 10 mN.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, it has also been shown that hemodynamic nitrate tolerance blocks several endogenous adaptive mechanisms underpinned by nitric oxide (NO) release such as the antiischemic effect of myocardial preconditioning 5,6 , the non-adrenergic, non-cholinergic relaxation of gastrointestinal sphincters 7 and yields a state of insulin resistance 1 . The latter was suspected to somehow relate to the meal-induced insulin sensitization phenomenon first described by Sadri & Lautt 8 , since it was widely accepted that the phenomenon was the most effective NO-dependent endogenous insulin sensitizing mechanism.…”
Section: Introductionmentioning
confidence: 99%